Unorganized loan markets and monetary policy instruments - Shahin, Wassim (1990)
The paper uses a portfolio balance model to examine the relationship between monetary policy instruments and the unorganized loan rate. Predicting the direction of the change in this rate as a result of varying a policy instrument is important, since this rate is one channel through which a change in a policy instrument transmits to real activity, and since the demand side of the money market is partially re-equilibrated through this change. Studies have not clearly emphasized the relationship between each of the policy instruments and this rate. The findings depart in some cases from existing studies and shed more light on the relationships among policy instruments, monetary aggregates and real activity.